Language Crisis and Romantic Ontology: the Case of Hofmannsthal - Martín Arnedo, Santiago (Revista de Filología Alemana, 2020)
The aim of this study is to analyze from an ontological-historiographic perspective the classic writing of Hofmannsthal Ein Brief, which symbolically inaugurates the crisis of confidence in language in Central Europe, especially in Vienna, at the beginning of the 20th century. In this sense, the Hegelian analysis of sense-certainty and his criticism of Romanticism allows an in-depth vision of the problem. Hofmannsthal stands next to the romantics, as he accepts silence as the only way out and claims the concrete-particular.